Impacto de la COVID 19 en la enseñanza y aprendizaje en una escuela intercultural bilingüe de la comunidad San Martín de Tipishca, pueblo Kukama Kukamiria 2020-2021 - Mozombite Ruiz, Wendy Darlene (2024)
This thesis investigates the impact of the COVID-19 pandemic on the teaching of educators and the learning of sixth-grade students at Educational Institution N° 60588, characterized as a Bilingual Intercultural Education (EIB) school of the Kukama Kukamiria indigenous people, located in the San Martín de Tipishca community, Parinari district, Marañón River basin, Loreto department, during the years 2020 and 2021. From an anthropological perspective, the research seeks to understand how the effects of the pandemic have influenced sociocultural and socioeducational dynamics in the implementation of EIB during the crisis. The research identified four relevant aspects where the educational impact was evident: a) access to distance education and technology: achievements and gaps; b) adaptation of teaching and learning methodologies; c) perspectives and participation of parents in the education of their children; and d) community participation and local knowledge. Additionally, this thesis developed a participatory research process that allowed for a better understanding of the complexity of the educational reality during the pandemic. The research approach was qualitative, descriptive in nature, with an ethnographic design. The population sample included 46 people, including authorities, students, teachers, parents, as well as indigenous elders and plant specialists. Semi-structured interviews, direct observation, and the Talking Map, including stop motion animation, were employed.